Recurrent Upper Extremity Thrombosis Associated with Overactivity: A Case of Delayed Diagnosis of Paget-Schroetter Syndrome - Himani Sharma; Abhinav Tiwari (Case Reports in Vascular Medicine)
Paget-Schroetter syndrome is thrombosis of the axillary-subclavian vein that is associated with strenuous and repetitive activity of the upper extremities. Overuse of the arm coupled with external compression results in microtrauma in the intima of the subclavian vein, resulting in the activation of the coagulation cascade. Diagnosis is usually made by Doppler ultrasound and the treatment involves thrombolysis, while routine surgical decompression of the thoracic outlet is controversial. In this report, we present a case of a patient who presented with a second episode of spontaneous right upper extremity deep venous thrombosis. The first episode was inadequately treated with oral anticoagulation alone. During the second episode, Paget-Schroetter syndrome was diagnosed, after careful review of his occupational history. He subsequently underwent angioplasty and decompression of thoracic outlet with no recurrence of thrombosis in a 12-month follow-up period.